2004
DOI: 10.1159/000081848
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the ACC/AHA Guidelines for Preoperative Cardiac Risk Assessment in a General Medicine Preoperative Clinic: Improving Efficiency and Preserving Outcomes

Abstract: Background: The American College of Cardiology/American Heart Association (ACC/AHA) publishes recommendations for cardiac assessment of patients undergoing noncardiac surgery with the intent of promoting evidence-based, efficient preoperative screening and management. We sought to study the impact of guideline implementation for cardiac risk assessment in a general internal medicine preoperative clinic. Methods: The study was an observational cohort study of consecutive patients being evaluated in an outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…64,65 It should be noted that this algorithm was not derived from a prospective study; rather, it was derived from the interpretation of data from various studies and the judgments of the committee members. 66 The few studies that have evaluated the reliability of the ACC/AHA algorithm have limitations: they had few cardiac events; they failed to demonstrate that the algorithm is effective in stratifying cardiac risk across the 3 strata proposed in the algorithm; and they did not compare the predictive accuracy of the ACC/AHA algorithm with the most accurate clinical risk indices (i.e., the Lee and Detsky indices).…”
Section: American College Of Cardiology / American Heart Association mentioning
confidence: 99%
“…64,65 It should be noted that this algorithm was not derived from a prospective study; rather, it was derived from the interpretation of data from various studies and the judgments of the committee members. 66 The few studies that have evaluated the reliability of the ACC/AHA algorithm have limitations: they had few cardiac events; they failed to demonstrate that the algorithm is effective in stratifying cardiac risk across the 3 strata proposed in the algorithm; and they did not compare the predictive accuracy of the ACC/AHA algorithm with the most accurate clinical risk indices (i.e., the Lee and Detsky indices).…”
Section: American College Of Cardiology / American Heart Association mentioning
confidence: 99%
“…They found that guidelines implementation reduced preoperative noninvasive diagnostic testing by 11% (P=0.01) and preserved a low rate of peri-operative cardiac complications. 7 Almanaseer 8 Hoeks S E conducted a survey to determine adherence to the ACC/AHA guidelines 2002 on peri-operative care in daily clinical practice. This survey showed poor agreement between ACC/AHA guideline recommendations and daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…26 Consensus statements on cardiac risk stratification including who should undergo screening and revascularisation and management of patients with implanted cardiac stents have been developed and widely disseminated. [27][28][29] Perhaps this focus and attention on identifying and intervening on cardiac risk has mitigated the associations of smoking-related cardiovascular events with mortality, in both smokers and never smokers. Similar attention has not been given to preoperative risk stratification for postoperative pulmonary events.…”
Section: Discussionmentioning
confidence: 99%